The effect of inertial inhomogeneity on the flutter of a cantilevered flexible plate - Howell, Richard; Lucey, Anthony; Pitman, Mark (Elsevier Ltd., 2011)
We study the effect of adding discrete structural mass on the linear stability of an otherwise homogeneous cantilevered-free flexible plate immersed in uniform axial flow. The methods of Howell et al. that mixed numerical simulation with eigenvalue analysis are simply extended for the present study. An ideal two-dimensional flow is assumed wherein the rotationality of the boundary-layers is modelled by vortex elements on the solid–fluid interface and the imposition of the Kutta condition at the plate’s trailing edge. The Euler– Bernoulli beam model is used for the structural dynamics. It is shown that addition of mass to the plate can be either stabilising or destabilising, depending upon the location of the added mass, and how its inclusion modifies the energy exchanges of the corresponding homogeneous structure. Our results therefore suggest a straightforward means by which the critical flow speed at which low-amplitude flutter sets in can be passively controlled in engineering applications.